Difficulty accessing crack pipes and crack pipe sharing among people who use drugs in Vancouver, Canada - Ti Lianping; Buxton Jane; Wood Evan; Zhang Ruth; Montaner Julio; Kerr Thomas (BMC, 2011)
Abstract Background Crack pipe sharing can increase health risks among people who use drugs, yet the reasons for sharing these pipes have not been well described. Therefore, we sought to identify the prevalence and correlates of crack pipe sharing among a community-recruited sample of people who use illicit drugs in Vancouver, a setting where crack pipes are provided at low or no cost. Findings Data for this study were derived from two prospective cohorts of people who use drugs: the Vancouver Injection Drug Users Study (VIDUS) and the AIDS Care Cohort to evaluate Exposure to Survival Services (ACCESS). Multivariate logistic regression was used to identify factors independently associated with crack pipe sharing. Among 503 crack users, 238 (47.3%) participants reported having shared a crack pipe in the previous six months. Having acquired a mouthpiece in the last six months (adjusted odds ratio [AOR] = 1.91; 95% confidence interval [CI]: 1.31 - 2.79) and difficulty finding new pipes (AOR = 2.19; 95%CI: 1.42 - 3.37) were positively associated with pipe sharing. Binge drug use (AOR = 1.39; 95%CI: 0.96 - 2.02) was marginally associated with sharing pipes. Discussion There was a high prevalence of crack pipe sharing in a setting where crack pipes are distributed at low or no cost. Difficulty accessing crack pipes was independently and positively associated with this behavior. These findings suggest that additional efforts are needed to discourage crack pipe sharing as well as increase access to crack pipes.